Jigsaw Learning Strategy and Secondary Schools Students’ Mathematics Achievement by Gender in Laikipia County, Kenya - Watetu Mbacho, Dr. Naomi (International Journal of Scientific Research and Management (IJSRM), 2022)
Gender differences in mathematics achievement have continued being a challenge in the society today. This difference has important implications for the under-representation of women in the field of science. In Kenya, students’ gender difference in mathematics achievement is evident in female students performing poorly in the subject in the Kenya Certificate of Secondary Education (K.C.S.E) examinations. That has raised concerns among the stakeholders in education due to the importance attached to mathematics. The factors that are attributed to the female students’ dismal performance in the subject include; poor attitude towards the subject by the students and teachers, gender stereotypes, lack of role models, low mathematics self-concept and the instructional methods used by teachers. This study sought to address the problem of ineffective instruction methods used by teachers and gender stereotypes. This is as a result of inadequate information in research conducted in Kenya on effects of the use of Jigsaw Cooperative learning Strategy on students’ achievement in mathematics by gender. Solomon Four non-equivalent control group design was used in the study. A simple random sample of four co-educational secondary schools was selected from Laikipia County. The sample size was 4 schools out of the possible 67 schools with a population of about 20,800 students in Laikipia County. A mathematics achievement test (MAT) for students was used to collect the required data. A total of 188 Form three secondary school students (i.e., 84 girls and 104 boys) wrote the MAT. The MAT was piloted in a school which was not used in the study in Laikipia County and it’s reliability estimated to be 0.95 using KR-21 formula. Data were analyzed using posttest mean and t-test at alpha (ά) level of .05. Gender did not affect students’ achievement in mathematics when students were taught using Jigsaw Cooperative Learning Strategy (t(92) = -.835, p=.423). The findings are expected to be useful to teachers in secondary schools because they will be able to identify learning strategies which will reduce gender disparities in learners’ mathematics achievement. Curriculum developers and education officers are likely to benefit from this study in deciding on the appropriate learning strategies for learners to improve the quality of mathematics in the country. The research recommends use of Jigsaw cooperative learning strategy in mathematics instruction in secondary schools in Kenya to improve and also reduce gender disparities in the mathematics achievement. Keywords: Jigsaw learning strategy, Mathematics achievement, Gender.